Rehabilitasi Kebun Kopi Guna Peningkatan Produksi di Desa Dukuhwaringin Kecamatan Dawe Kabupaten Kudus - Shodiq Eko Ariyanto; Pangestin Setyo Winastuti (Muria Jurnal Layanan Masyarakat, 2020)
The main production of farmers in Dukuhwaringin Village, Dawe District, Kudus Regency is coffee. The partner of this activity is Robusta type community coffee farmers who are members of two farmer groups, that is Muria Jaya farmer group and Sido Makmur farmer group. The application of Appropriate Technology is carried out in June - December 2019. The method applied includes the socialization / extension of coffee pruning technology, training, demonstration plot, application in post-harvest coffee pruning. The results of the TTG pruning activities carried out included in the category of light pruning. Coffee plants have evenly distributed and balanced branch conditions that greatly affect the results of production estimates. Many branches must be pruned because the branches are old and have a diseases. After pruning, the plants produce new shoots. The branches that are pruned at this time greatly affect the number of branches and production for the following year.